Sikap Siswa terhadap Pembelajaran Matematika melalui Model Pembelajaran Novick - Sri Rezeki; Mutia Mutia (ARITHMETIC: Academic Journal of Math, 2020)
Students' attitudes towards learning mathematics greatly affect student learning outcomes. If the attitude of students in the learning process gives a positive response, it will be easy for students to understand the material presented by the teacher, and vice versa if students give a negative response, then students will find it difficult to understand the material presented. This study aims to determine students' attitudes towards learning activities by applying the Novick learning model. This type of research is a type of qualitative research. The method used in this research is distributing questionnaires to students. The results showed that the students' attitudes towards Novick's learning model were quite positive. Students generally expressed their joy and enthusiasm in participating in the Novick learning model.